Novel non-antibiotic triple therapy for Helicobacter pylori-positive functional dyspepsia patients resistant to conventional antibiotic treatments: an exploratory pilot study - Zhan, Canyu; Huang, Yurong; Yang, Zhengyi; Wu, Hua; Zheng, Juan; Yang, Wangliu; Rao, Junjie; Song, Gengqing; Yang, Jie (Frontiers in Medicine, 2026)
PurposeThe rising antibiotic resistance has significantly reduced the efficacy of standard bismuth-based quadruple therapy for Helicobacter pylori (H. pylori) infections, particularly in patients with multiple eradication failures. This study evaluates a novel non-antibiotic triple therapy comprising Weisu granules, berberine hydrochloride, and Bio-Three—a probiotic formulation containing Clostridium butyricum TO-A, Enterococcus faecalis T-110, and Bacillus mesentericus TO-A—in treating H. pylori-positive functional dyspepsia (FD) patients resistant to conventional antibiotic treatments.Patients and methodsA two-center retrospective analysis involved 48 FD patients who had previously failed at least two H. pylori eradication therapies. Participants underwent a 14-day course of non-antibiotic therapy, with primary endpoints being H. pylori eradication rate, assessed via 14C urea breath test, and secondary endpoints including symptom relief and adverse reactions.ResultsSuccessful H. pylori eradication was achieved in 72.9% (35/48) of patients. Symptom relief was observed in 77.08% of cases, with 43.75% achieving effective improvement and 33.33% marked improvement. Adverse reactions were mild, occurring in 8.3% (4/48) of patients, including abdominal distension, dry mouth, and nausea, all resolving spontaneously. The compliance rate was high at 91.67%.ConclusionThis study provides preliminary evidence supporting the use of non-antibiotic triple therapy as an alternative for managing H. pylori infections in FD patients resistant to conventional antibiotic treatments, demonstrating notable eradication rates and symptom relief with minimal adverse effects. Further research is warranted to explore its mechanisms, long-term efficacy, and potential integration into existing treatment paradigms.